Rewritable Triple-Mode Light-Emitting Display - Lee, Seokyeong; Park, Jong Woong; Jang, Jihye; Oh, Jin Woo; Kim, Gwanho; Yoo, Jioh; Jung, Jong Gun; Han, Hyowon; Jiang, Wei; Lee, Chang Eun; Yoon, Jungwon; Zhao, Kaiying; et al. (Nano-Micro Letters, 2025)
Despite great progress in developing mode-selective light emission technologies based on self-emitting materials, few rewritable displays with mode-selective multiple light emissions have been demonstrated. Herein, we present a rewritable triple-mode light-emitting display enabled by stimuli-interactive fluorescence (FL), room-temperature phosphorescence (RTP), and electroluminescence (EL). The display comprises coplanar electrodes separated by a gap, a polymer composite with FL inorganic phosphors (EL/FL layer), and a polymer composite with solvent-responsive RTP additives (RTP layer). Upon 254 nm UV exposure, a dual-mode emission of RTP and FL occurs from the RTP and EL/FL layers, respectively. When a polar liquid, besides water, is applied on the display and an AC field is applied between the coplanar electrodes, EL from the EL/FL layer is triggered, and the display operates in a triple mode. Interestingly, when water is applied to the display, the RTP mode is deactivated, rendering the display to operate in a dual mode of FL and EL. By manipulating the evaporation of the applied polar liquids and water, the mode-selective light emission of FL, RTP, and EL is rewritable in the triple-mode display. Additionally, a high-security full-color information encryption display is demonstrated, wherein the information of digital numbers, letters, and Morse code encoded in one optical mode is only deciphered when properly matched with that encoded in the other two modes. Thus, this article outlines a strategy to fulfill the substantial demand for high-security personalized information based on room-temperature multi-light-emitting displays. Highlights: 1 A rewritable triple-mode light-emitting display (RE-TriLED) was fabricated, enabled by stimuli-interactive fluorescence (FL), room-temperature phosphorescence (RTP), and electroluminescence (EL). 2 Mode-selective multiple light emission is achieved, in which the three emission modes of FL, RTP, and EL are readily manipulated through the controlled evaporation of polar liquids and water. 3 A high-security, full-color information encryption display is demonstrated, wherein optical information encoded in one mode is decipherable only when properly aligned with the other two modes.